Hukuman Mati bagi Koruptor Perspektif Ayat Al-Qur’an - Khusnan, Muhammad Ulinnuha (SUHUF, 2012)
The death penalty for the corruptors is allegedly able to provide a deterrent effect and a sense of justice for the people. It is in essence, because the corruptors do not only spend the money of the state, but slowly but sure also in fact, Ã¢â‚¬Å“killÃ¢â‚¬Â the innocent people. Constitutionally, the Law/Regulation number 31 of 1999 junto the Law/Regulation number 20 of 2001 concerning the act of Corruption have included the death penalty as one of the options of the form of punishment for the corruptors. However, practically, until today, there is no even single corruptor who is sentenced to death in this country. This paper will specifically discuss the perspective and the signal of the Qur'anic verses on the death penalty for the corruptors, and how its implementation in Indonesia is.